Pemanfaatan Limbah Kulit Kopi dan Tempurung Kelapa menjadi Briket Biomassa - Furqan, Muhammad Haikal; Elfiana, Elfiana; Amalia, Zuhra (Jurnal Teknologi, 2025)
Non-renewable fuel energy that is increasingly depleted is a concern of many people and many practitioners and academics are starting to try to make alternative fuels derived from renewable resources. The process of making briquettes from coffee skin waste and coconut shells has been carried out by the carbonization method. To find the effect of variations in raw materials on the quality of briquettes and to find what is the best adhesive content on the quality of briquettes produced includes several tests, namely water content, ash content, calorific value and burning rate based on SNI. The manufacture of coffee husk and coconut shell briquettes was carried out with variations of raw materials 0: 100, 25: 75, 50: 50, 75: 25, 100: 0 and adhesive variations of 8%, 10%, 12%, 14% and 16%. From the test results, the ratio of raw materials is good in the ratio of 0:100, 25:75 and 50:50 with 8%-12% adhesive. With the test results of water content 4.36 - 7.06 (%), the results of ash content 3.74 - 6.18 (%), the results of the combustion rate 0.257 - 0.215 (g/min), and the results of calorific value 6345.99 - 5705.94 (cal/g).